Aplikasi Media Pembelajaran Aksara Sunda Berbasis Android - Arini Habibah; Dian Nur Sholihaningtias; Noor Komari Pratiwi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
The Sundanese script is the work of orthography of Sundanese people since around the 5th century AD until today. However, the lack of interesting and motivating media to learn scripts, both printed and electronic, makes the Sundanese script endangered. With the rapid development of technology and the era of digitalization as today, most Indonesian people have smartphones with Android operating systems that are easy to carry anywhere. Android is not only used as a communication and entertainment tool, but also as a method that can be developed as a learning medium that can convey learning material textually, and audio-visually. The purpose of this research is to design an easy-to-use Sundanese script learning media application and to implement an Android-based Sundanese script learning media application so that the public is interested in learning Sundanese script. The method used for application development is MDLC (Multimedia Development Life Cycle) multimedia application in education which consists of 6 stages, including Concept, Design, Material Collecting, Assembly, Testing and Distribution. The result obtained from this study is the Android-based application of Sundanese script learning media. The application has been tested with alpha test and from the results of the test, it can be concluded that the public can easily learn the Sundanese script with an attractive appearance because this application is equipped with audio pronunciation of the Sundanese script.